Clinical Pharmacogenetics for Precision Medicine: Successes and Setbacks. (23rd October 2019) - Chambliss, Allison B; Marzinke, Mark A
Abstract: Background: Pharmacogenetics is a key component in the delivery of therapeutics to maximize pharmacologic efficacy and minimize toxicity. There are numerous identified gene–drug pairs that demonstrate the utility of pharmacogenetics testing for drug or dose selection. Although some of these pairs have translated into clinical use, pharmacogenetic testing has not yet made its way into routine clinical practice at many institutions. Content: This review provides an overview of clinically actionable pharmacogenetics in precision medicine. Examples of successfully implemented gene–drug pairs, along with common testing methodologies and guidelines for application, are discussed. Remaining barriers to widespread clinical implementation are also examined. Summary: There is a recognized role for genotyping in the guidance of therapeutic drug regimens and the prevention of adverse drug reactions. Evidence-based guidelines are available to aid in the selection of treatment upon pharmacogenetics testing for established gene–drug pairs. Multidisciplinary clinical collaboration and clinical decision support tools will be critical for widespread adoption, and financial reimbursement barriers remain.